Anticipating Divine Protection? Reminders of God Can Increase Nonmoral Risk Taking. (April 2015) - Kupor, Daniella M.; Laurin, Kristin; Levav, Jonathan
Religiosity and participation in religious activities have been linked with decreased risky behavior. In the current research, we hypothesized that exposure to the concept of God can actually increase people's willingness to engage in certain types of risks. Across seven studies, reminders of God increased risk taking in nonmoral domains. This effect was mediated by the perceived danger of a risky option and emerged more strongly among individuals who perceive God as a reliable source of safety and protection than among those who do not. Moreover, in an eighth study, when participants were first reminded of God and then took a risk that produced negative consequences (i.e., when divine protection failed to materialize), participants reported feeling more negatively toward God than did participants in the same situation who were not first reminded of God. This research contributes to an understanding of the divergent effects that distinct components of religion can exert on behavior.